Rancangan Bangun Aplikasi Berbasis Mobile Pengukur Kualitas Rekam Medis Di Rumah Sakit Aisyiyah Siti Fatimah Tulangan - Ilmi, Laili Rahmatul; Ismail, Maura Aulia; Nisak, Umi Khoirun (Akademi Perekam dan Informasi Kesehatan Imelda, 2026)
The quality of medical record completeness is very vital, hence it needs to be taken seriously. Sifi Fatimah Tulangan Hospital focuses on quality control, necessitating innovation to facilitate users in maintaining quality, which is achieved through the design and development of a mobile-based medical record quality measurement application. This research aims to assist in monitoring and evaluating the quality and completeness of medical record filling. This type of research is action research with a Research and Development (RnD) design. There are 8 steps involved in this research, starting with primary data collection through interviews with users using an interview guide to understand their needs as a basis for designing and developing the mobile-based application. Subsequently, 7 steps are taken to produce products, including initial design, creating user flow, creating use case diagrams, creating activity diagrams for mobile-based UI (User Interface) design, and designing the application wireframe.Needs as the basis for designing and building mobile-based applications, followed by 7 steps taken to produce products including initial design, creating user flow, creating use case diagram, creating activity diagram for mobile-based UI (User Interface) design, designing wireframe for medical record quality measurement application, conducting design using Figma application, and the results of the trials. The design results that meet the needs are then developed by the IT department at the hospital, and the output of this research is a journal and intellectual property rights.